KAJIAN SIFAT FISIKA TANAH SUB DAS AIR BATANANG DAS SUMPUR KECAMATAN BATIPUH KABUPATEN TANAH DATAR - Yulnafatmawita Yulnafatmawita; Amrizal Saidi; Al Asfhihani Elnita (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2009)
Excessive utilization of natural resource by human being will affect the sustainability of agriculture, land and environment. This is due to degradation of soil physical properties in the area. A research about study of soil physical properties had been taken out in a sub-sub watershed Batanang of Sumpur watershed, Batipuh, Tanah Datar Regency, in West Sumatra. The research was conducted by surveying the area in 2006. Disturbed and undisturbed soil samples were taken in different land units. Then, soil samples were analysed at soil laboratory, Agriculture College, Andalas University Padang. The result showed that all of land units in this sub sub watersehed had the same soil texture class, that was fine clay. The bulk volume of the soil was higher in Mixed woodland unit than those in forest land units. Permeability value of the soil was higher at forest from all degrees of slope than that at mixed woodland, even though soil organic matter content of mixed woodland unit higher than that at forest with 25-45% slope.Keywords: Sub watershed (DAS), forest, land unit, soil physical properties